How academic biologists and physicists view science outreach. - Elaine Howard Ecklund; Sarah A James; Anne E Lincoln (PLoS ONE, 2012)
Scholars and pundits alike argue that U.S. scientists could do more to reach out to the general public. Yet, to date, there have been few systematic studies that examine how scientists understand the barriers that impede such outreach. Through analysis of 97 semi-structured interviews with academic biologists and physicists at top research universities in the United States, we classify the type and target audiences of scientists' outreach activities. Finally, we explore the narratives academic scientists have about outreach and its reception in the academy, in particular what they perceive as impediments to these activities. We find that scientists' outreach activities are stratified by gender and that university and disciplinary rewards as well as scientists' perceptions of their own skills have an impact on science outreach. Research contributions and recommendations for university policy follow.